Poly(n-butyl methacrylate) with primary amine end groups for supporting cell adhesion and proliferation of renal epithelial cells. Issue 15 (13th October 2017) - Cox-Nowak, Kayleigh; Al-Yamani, Ohood; Grant, Colin A.; Green, Nicola H.; Rimmer, Stephen
ABSTRACT: Polymer coatings that support epithelial cell culture have been developed. Ozonolysis and subsequent workup of poly(butyl methacrylate- co -butadiene) copolymers is used to form oligomers with carboxylic acid end groups, which are then further reacted with diamines to provide poly(butyl methacrylate)s with primary amine end groups. The polymers are cast as films and used as cell culture substrates for human dermal fibroblasts and human renal epithelial cells. Fibroblast and epithelial cells adhere and proliferate on acid functional materials but on amine functional films epithelial cells show greater viability than fibroblasts. GRAPHICAL ABSTRACT: